IMPACT OF GRID-FORMING INVERTERS ON IMPEDANCE- BASED ANALYSIS METHODS IN INVERTER-DOMINATED POWER SYSTEMS - Herlina
The increasing penetration of renewable energy in the past decade has brought significant changes to the landscape of power systems. The large-scale integration of Photovoltaic-Battery Energy Storage Systems (PV-BESS) has become one of the main drivers, with PV serving as a clean renewable energy source and batteries providing flexible energy storage. The declining cost of solar panels, improvements in battery efficiency, and supportive policies from various countries have accelerated the adoption of PV-BESS. However, the dominance of inverters as the interface connecting PV-BESS to the grid introduces new challenges, particularly in small-signal stability. Unlike conventional synchronous generators, which possess high natural inertia, inverters lack inherent inertia, making the system more susceptible to small disturbances and complex, unpredictable dynamics. In this context, the Grid Forming Inverter (GFM) emerges as a key component offering potential solutions. GFMs can independently form voltage and frequency, mimicking the behavior of synchronous generators, thereby providing virtual inertia and enhancing system stability. However, comprehensive understanding of the impact of key GFM parameters—such as inertia, damping, and frequency droop—on small-signal stability remains limited. These challenges become even more complex when systems operate under various dynamic set points that reflect changing load and generation conditions, especially when inverter internal details are unavailable (black box scenarios). Moreover, weak grid conditions, characterized by relatively high grid impedance and low stability margins, further complicate ensuring system stability.